Enhancing performance and user convenience of multi-biometric verification systems - Hossain, Shafaeat; Phoha, Vir V. (Pattern Analysis and Applications, 2021)
A multi-biometric verification system lowers the verification errors by fusing information from multiple biometric sources. Information can be fused in parallel or serial modes. While parallel fusion gives a higher accuracy, it may suffer from a serious problem of taking a longer verification time. Serial fusion can alleviate this problem by allowing the users to submit a subset of the available biometric characteristics. Unfortunately, several studies show that serial fusion may not reach the level of accuracy of parallel fusion. In this paper, we propose a fusion framework which combines the advantages of both parallel and serial fusion. The core of the framework is a new concept of “confident reject region” which incurs nearly zero verification error. We evaluate our framework by performing experiments on two multi-biometric verification systems built with NIST biometric scores set release 1. The experimental results show that our framework achieves a lower equal error rate and takes a shorter verification time than standard parallel fusion. © 2021, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.
Keywords: dept.csc; peer-reviewed